Enhancing the Quality of Life of Older Persons with and Without a Disability through Adapted Physical Activity Across Europe - Herman Van Coppenolle; Stefka Djobova; Iana Dobreva (Lithuanian Sports University, 2018)
Research data estimate that by the end of 2040 the severely impaired adults will be 6.5% of the total population in Europe, or 24.5 million people. Today 7.5% of the total European population is 75 years old and more. In 30 years this percentage will rise to 14.4%. Ageing is a process that often affects and restricts the people who are growing old, on physical, psychological and social level. As older adults are the fastest growing group, attention needs to be given to them as a special population in the area of exercise and sport. The review article aims to present research data in intervention and prevention of disease and disability in older persons through adapted physical activity as well as analyze some theoretical models for changing physical inactivity into an active lifestyle in older people. As analysis of literature showed, all older adults at all ages should be encouraged to move more, and increase aspects of physical activity in their lives; this may be balance and posture, strength training, or moderate or / and vigorous intensity activities, but it is important to maintain a regular habit throughout older years. Specific targets should be tailored to the capacity, the motivation, expectations and confidence in older individuals, in all societies and demographic groups. The research data about the benefits of physical activity are clear and convincing. Till now there is a need to act and find the best strategy and policy to realize this active lifestyle leading to a better health and more well-being. Keywords: ageing, disability, adapted physical activity, thematic network.